Evaluating the Vestibulo-Ocular Reflex Following Traumatic Brain Injury: A Scoping Review. (10th November 2021) - Crampton, Adrienne; Garat, A.; Shepherd, H. A.; Chevignard, M.; Schneider, K. J.; Katz-Leurer, M.; Gagnon, I.J.
ABSTRACT: Purpose: To identify the tests and tools used to evaluate vestibulo-ocular reflex (VOR) function after traumatic brain injury (TBI) in all age groups and across TBI severity. Methods: An electronic search was conducted to include relevant peer-reviewed literature published up to November 2019. Studies included those done with humans, of all ages, and had assessments of oculomotor and/or vestibulo-ocular function in TBI. Results: Of the articles selected (N = 48), 50% were published in 2018/2019. A majority targeted mild TBI, with equal focus on non-computerized versus computerized measures of VOR. Computerized assessment tools used were videonystagmography, dynamic visual acuity/gaze stability, rotary chair, and caloric irrigation. Non-computerized tests included the head thrust, dynamic visual acuity, gaze stability, head shaking nystagmus, rotary chair tests and the vestibular/oculomotor screening tool. High variability in administration protocols were identified. Namely: testing environment, distances/positioning/equipment used, active/passive state, procedures, rotation frequencies, and variables observed. Conclusions: There is a rapid growth of literature incorporating VOR tests in mild TBI but moderate and severe TBI continues to be under-represented. Determining how to pair a clinical test with a computerized tool and developing standardized protocols when administering tests will help in developing an optimal battery assessing the VOR in TBI.